Low-frequency theta oscillations in the human hippocampus during real-world and virtual navigation - Véronique D. Bohbot (Nature Portfolio, 2017)
Rhythmic oscillations in theta frequency range (7–9 Hz) are observed in rodents during navigation. Here the authors demonstrate robust similar theta rhythmicity in human hippocampus during both real and virtual movements.